Effects of carbon concentration and transformation temperature on incomplete transformation and crystallography of low-carbon bainitic steel - Binbin Wu; Tianyu Zhou; Zhiquan Wang; Xuelin Wang; Chengjia Shang; Yishuang Yu; Maged Elhefnawey; Li Li (Journal of Materials Research and Technology, 2024)
A close relationship exists between the crystallographic characteristics of a bainitic matrix and formation of martensite/austenite (M/A) constituents. In this work, the isothermal transformation kinetics and crystallographic characteristics of low-carbon bainitic (LCB) steel were investigated to elucidate the formation mechanism of M/A constituents and twin-related V1/V2 variant pairs (Σ3 boundaries). The formation of M/A constituents depends on the bainitic transformation kinetics, which are influenced by the carbon concentration and isothermal temperature. An increase in the carbon concentration or transformation temperature promotes the formation of blocky M/A constituents by increasing the activation energy of the grain boundary and autocatalytic nucleation processes. In addition, increasing the carbon concentration or lowering the transformation temperature increases the strength of the austenite phase and promotes autocatalytic nucleation, thereby producing more twin-related V1/V2 variant pairs. Therefore, the increase in the carbon concentration increases the number of twin-related V1/V2 variant pairs while also causing the formation of blocky M/A constituents. To overcome this limitation, a novel heat treatment process design is proposed that can significantly eliminate blocky M/A constituents and generate high-density twin-related V1/V2 variant pairs.